Interpopulational and seasonal variation in the chemical signals of the lizard Gallotia galloti - Roberto García-Roa (PeerJ, 2017)
Communicative traits are strikingly diverse and may vary among populations of the same species. Within a population, these traits may also display seasonal variation. Chemical signals play a key role in the communication of many taxa. However, we still know far too little about chemical communication in some vertebrate groups. In lizards, only a few studies have examined interpopulational variation in the composition of chemical cues and signals and only one study has explored the seasonal effects. Here we sampled three subspecies of the Tenerife lizards (Gallotia galloti) and analyze the lipophilic fraction of their femoral gland secretions to characterize the potential interpopulational variation in the chemical signals. In addition, we assessed whether composition of these secretions differed between the reproductive and the non-reproductive season. We analyzed variations in both the overall chemical profile and the abundance of the two main compounds (cholesterol and vitamin E). Our results show interpopulational and seasonal differences in G. gallotia chemical profiles. These findings are in accordance with the high interpopulational variability of compounds observed in lizard chemical signals and show that their composition is not only shaped by selective factors linked to reproductive season.